2014
DOI: 10.5560/znc.2013-0115
|View full text |Cite
|
Sign up to set email alerts
|

Flavone Composition and Antihypercholesterolemic and Antihyperglycemic Activities of Chrysanthemum coronarium L.

Abstract: Five flavones were isolated from Chrysanthemum coronarium L., four of which were isolated for the first time from the genus Chrysanthemum. Two were the flavonoid aglycones 5,7- dihydroxy-3,6,4’-trimethoxyflavone (1) and scutellarin-6,7-dimethyl ether (2). A new flavonoid glycoside, apigenin-7-O-[2’’(6’’’-O-b-ß-acetylglucopyranosyl)]-6’’-O-acetylglucopyranoside (3), along with two known ones, i. e. apigenin-7-O-(2’’-O-b-ß-glucopyranosyl)-b-ß-glucopyranoside (4) and 6-methoxy quercetin-7-O-b-ß-glucopyranoside (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It has long been prescribed for the treatment of eye diseases in Chinese traditional preparations. Recent studies have shown that flavonoids in chrysanthemum are more likely to contribute to curing eye diseases [1] , [21] , [23] , [30] , [41] . Despite of recent progress, the definite component of chrysanthemum and the mechanism of action in the way chrysanthemum contributes to vision remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been prescribed for the treatment of eye diseases in Chinese traditional preparations. Recent studies have shown that flavonoids in chrysanthemum are more likely to contribute to curing eye diseases [1] , [21] , [23] , [30] , [41] . Despite of recent progress, the definite component of chrysanthemum and the mechanism of action in the way chrysanthemum contributes to vision remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…After injection, animals had free access for food, water and were given 5% glucose solution to drink overnight to encounter hypoglycemic shock. Animals were checked daily for the presence of glycosuria [14]. Animals were considered to be diabetic if glycosuria was present for 3 consecutive days.…”
Section: Induction Of Hyperglycemiamentioning
confidence: 99%
“…Group 4: Rats were considered as hyperglycemic (HG)-HC which classified as follows: Groups 5 and 6: HG-HC group rats oral administered 250 mg/kg BW crude ethanol extracts of MGE and NPE for 30 days, respectively. Group 7: HG-HC rats orally administered 2 mg/kg BW of the anti-HC reference drug; atorvastatin [4,14] and the anti-HG glibenclamide reference drug at the dose of 10 mg/kg BW daily for 30 days [13,14].…”
Section: Dose Regimens and Route Of Administrationmentioning
confidence: 99%
“…Flavanols and flavonols, condensed tannins (proanthocyanidins), hydrolysable tannins (ellagitannins and gallotannins), stilbenes, anthocyanins, and phenolic acids were reported as the most commonly found polyphenols in Morus fruits [13]. Polyphenols content may reduce plasma TG, TC, and LDL-C in hyperlipidemic rats [15,44].…”
Section: Discussionmentioning
confidence: 99%